PENGARUH AGAMA SAMAWI TERHADAP PERUBAHAN SOSIAL-BUDAYA DI ASSOLOKOBAL LEMBAH BALIM - Albertus Heriyanto (Khazanah: Jurnal Studi Islam dan Humaniora, 2016)
Abstract: Before their encounter with the immigrants, the Balim religious lifecentered in their honai adat (traditional house). However, since the presence ofdivine religions, the center of their ritual and spiritual life is devolving to churchesor mosques, and marginalizes the role of the honai adat. The presence of divinereligions has contributed to peoples way of life, especially in broadening theperspective of the Balim about human beings. The extent of human relationsperspective has played a major role in relativizing the influence of traditionalvalues to their ways of thinking and behaving. With few exceptions, the generalcolor manifested in the relationship between the two belief systems is thedominance of the divine religions to local one. Conversion to the divine religionsand process of community building in one religion is not merely a faith event,but also part of the cultural process, part of a strategy to open an access toa better life in economy, socio-politics, or even in spiritual aspects. In this case,the divine religions are challenged to present their faces as the ways of salvationwhich is humane and civilized.